2006
DOI: 10.1001/archneur.63.4.533
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Global N-Acetyl Aspartate With Cognitive Impairment in Multiple Sclerosis

Abstract: Background: Whole-brain N-acetyl aspartate (NAA), a measure of neuronal function, can be assessed by multislice echo-planar spectroscopic imaging. Objective: To test the hypothesis that the global brain NAA/creatine (Cr) ratio is a better predictor of cognitive dysfunction in multiple sclerosis than conventional magnetic resonance imaging measures. Design: Survey. Setting: Research-oriented hospitals. Patients: Twenty patients, 16 women and 4 men (mean age, 36 years), with early relapsing-remitting multiple sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 25 publications
(29 reference statements)
0
29
0
3
Order By: Relevance
“…NAA also falls in gray matter, perhaps accounting for cognitive defects often recorded in multiple sclerosis patients (Staffen et al, 2005). Assays of whole-brain NAA using MRI have shown that cognitive impairment in multiple sclerosis correlates with reductions in NAA content (Mathiesen et al, 2006b). While atrophy and loss of NAA are both features of multiple sclerosis, the degree of loss of whole-brain NAA exceeds the development of atrophy by several fold, encouraging the conclusion that neuronal dysfunction may precede tissue loss in multiple sclerosis (Mathiesen et al, 2006a).…”
Section: Magnetic Resonance Spectroscopy and Imaging Of Naamentioning
confidence: 99%
See 1 more Smart Citation
“…NAA also falls in gray matter, perhaps accounting for cognitive defects often recorded in multiple sclerosis patients (Staffen et al, 2005). Assays of whole-brain NAA using MRI have shown that cognitive impairment in multiple sclerosis correlates with reductions in NAA content (Mathiesen et al, 2006b). While atrophy and loss of NAA are both features of multiple sclerosis, the degree of loss of whole-brain NAA exceeds the development of atrophy by several fold, encouraging the conclusion that neuronal dysfunction may precede tissue loss in multiple sclerosis (Mathiesen et al, 2006a).…”
Section: Magnetic Resonance Spectroscopy and Imaging Of Naamentioning
confidence: 99%
“…Assays of whole-brain NAA using MRI have shown that cognitive impairment in multiple sclerosis correlates with reductions in NAA content (Mathiesen et al, 2006b). While atrophy and loss of NAA are both features of multiple sclerosis, the degree of loss of whole-brain NAA exceeds the development of atrophy by several fold, encouraging the conclusion that neuronal dysfunction may precede tissue loss in multiple sclerosis (Mathiesen et al, 2006a). Studies employing NAA measurements appear to provide a better correlation with disability in MS patients than do MRI measures of lesion load (Wolinsky and Narayana, 2002).…”
Section: Magnetic Resonance Spectroscopy and Imaging Of Naamentioning
confidence: 99%
“…[33][34][35] Cognitive impairment has significant negative ramifications at multiple levels. Finding a definition of impairment that could most accurately identify patients for a more comprehensive neuropsychological evaluation has significant importance.…”
Section: Versus Psimentioning
confidence: 99%
“…Such measures show relatively stronger correlations with clinical measures of disability (i.e., cognitive dysfunction and physical disability) than do conventional MRI measures. [71][72][73][74][75][76][77][78] Longitudinal studies suggest that MRS measures hold promise in predicting the development of disability. [71][72] MRS is just beginning to be applied to the study of the spinal cord in patients with MS (e.g., see section on "Spinal cord imaging" as follows for details).…”
Section: Mrsmentioning
confidence: 99%